Exploring the Phenomenon of Fear of Missing Out (FoMO): The Emergence, Practice, and its Impact on Social Media User - Ida Rosida; Anggi Nauli Harahap; Eli Alfiyanti; Yuke Aysa Wattimury; Sartika Pratiwi (Insaniyat : Journal of Islam and Humanities, 2022)
This article discusses the phenomenon of Fear of Missing Out (FoMO) on social media. It is a term used to show human consumption behavior who are afraid of missing things including gaining social interaction, buying commodities, and others as it has emerged in social media. Thus, this paper aims to explore and investigate the phenomenon of Fear of Missing Out. This research used Systematic Literature Review (SLR) as the reproducible and explicit method to answer the topic of the research by evaluating, identifying, and synthesizing all related documents and publications by the researchers, and scholars. The research conducts an in-depth study of the articles which have been published in the last ten years and recent FoMO cases that occurred and were reported on local news, articles, and social media. This research reveals the emergence of the phenomenon of FoMO in social media, the practice of FoMO that appear in Instagram features, and the impact of FoMO on social media user. These fndings show that the FoMO phenomenon emerges with the highest fear of missing information, interaction, relatedness, popularity, and opportunity on social media, especially on Instagram. In addition, FoMO harms social media users regarding mental health such as experiencing mental illness, anxiety, depression, and insecurities in comparing life with others. In conclusion, the phenomenon of fear of Missing Out inﬂuences the user negatively as it is harmful to both emotional and psychological.